أثر مقاصد الشريعة في آراء الإمام ابن عاشور وترجيحاته الأحوال الشخصية أنموذجا - يعقوب، سركوت سروك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research examines the concept of maqasid al-shari'ah (higher intents and objectives of Shari'ah) and its impacts on the study of Islamic jurisprudence in the light of the viewpoint of al-Imam MoÍammad al-Tahir Ibn 'Ashur. It begins with discussing various important aspects of his life and his intellectual efforts and thus analyzes some allegations directed against him. This research finally embarks on a discussion of maqasid in the light of Ibn 'Ashur's ideas. In this regard, it analyzes the debates on this subject that had gone before Ibn 'Ashur and their influences on him, those during his time and the continuous discussion on the subject after him. One important finding of this study is that, Ibn 'Ashur never wanted maqasid to be an alternative the studies of principles Islamic jurisprudence. It also emerges that, in his opinions and juristic preferences, Imam Ibn 'Ashur did not contradict or discredit the views of Imam Malik. Nor did he exclude himself from the Maliki school of law. Importantly, the findings of this research suggest that Imam Ibn 'Ashur did not intend to give the discourse of maqasid the preeminent status that it enjoys in contemporary studies.